Indigenous goats: Productivity in traditional livestock systems of semi-arid Africa - Wilson, R.T. (1984)
The production performance of indigenous goats under sedentary and transhumant management systems in Sudan, Mali and Kenya are investigated. Age at first parturition was 15.5 months in Mali but was delayed to 18 months in Kenya where management was better. Kidding intervals were 7.8, 10.6 and 9 months respectively for Sudan, Kenya and Mali. Average litter sizes were 1.57, 1.25 and 1.20. Annual kidding rate for each country was estimated at 2.4, 1.4 and 1.6 per breeding female. Death rates in young kids were in excess of 30 percent overall. Daily weight gain to 5 months was about 80 g in Sudan, 50 g in Kenya and 60 g in Mali. There is a wide genetic base, from which selection for improvement can be made within these countries.